2022
DOI: 10.1017/ipm.2021.85
|View full text |Cite
|
Sign up to set email alerts
|

Profiling third-level student mental health: findings from My World Survey 2

Abstract: Objectives: This study aimed to identify risk and protective factors for mental health across student cohorts to guide mental health provision. Methods: Cross-sectional data from the My World Survey 2-Post Second Level (MWS2-PSL) were used. The sample consisted of N = 9935 students (18–65 years) from 12 third-level institutions (7 out of 7 universities and 5 out of 14 Institute of Technologies (IoTs)) across Ireland. Key outcomes of interest were depression, anxiety and suicidality. Risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Suicidal behaviour was particularly high among students in the IT in the ROI. A recent study conducted among third level students in Ireland, found that students attending Institutes of Technology had poorer mental health [38]. Furthermore, the IT has the highest proportion of students from a disadvantaged area, when compared to other higher education institutes in the ROI [39], which may partially explain the elevated prevalence rates revealed in the current study.…”
Section: Discussionmentioning
confidence: 62%
“…Suicidal behaviour was particularly high among students in the IT in the ROI. A recent study conducted among third level students in Ireland, found that students attending Institutes of Technology had poorer mental health [38]. Furthermore, the IT has the highest proportion of students from a disadvantaged area, when compared to other higher education institutes in the ROI [39], which may partially explain the elevated prevalence rates revealed in the current study.…”
Section: Discussionmentioning
confidence: 62%
“…The response to these items was dichotomous (yes/no). This set of items has been previously used in the same population cohort (Mahon et al, 2022).…”
Section: Self-harmmentioning
confidence: 99%
“…The number of students in Higher Education Institutions (HEIs) with serious mental health problems has risen significantly over the last decade (Andersen et al, 2021;Bekkouche et al, 2022;Lewis et al, 2021;ONS, 2022) and worsened due to stressors associated with the COVID-19 pandemic (Grubic et al, 2020;Salimi et al, 2023). Student counselling and wellbeing services have reportedly seen an increasing number of students with more severe mental health problems (Hill et al, 2020;Johnson & Lester, 2022;Mahon et al, 2022).…”
Section: Introductionmentioning
confidence: 99%